Vrednotenje življenjske dobe lesa, zaščitenega z emulzijami voskov in bakeretanolaminskimi pripravki v tretjem razredu izpostavitve - Lesar, Boštjan (Zbornik gozdarstva in lesarstva, 2010)
In our research, service life of wood exposed outdoor in the third use class, determined with double layer test, was investigated. In the first part of the investigation, Norway spruce wood specimens were impregnated with montan and polyethylene water based wax emulsion in combination with boron compounds. In the second part of the research, Norway spruce wood samples were impregnated with a copper-ethanolamine (Silvanolin) water based solution and aqueous solutions of individual components. For comparison, untreated Norway spruce, larch, beech and oak wood specimens were exposed as well. During exposition time, climate data under specimens and at weather station were recorded. The results showed that impregnation with wax emulsions and copper based solutions prolongs service life of wood, but protection with copper-ethanolamine solutions is considerably better. Resistance of wood, preserved with wax emulsions and copper-ethanolamine solutions, was influencedby concentration of emulsions/solutions and wood quality. The parallel measurements of wood moisture content and wood temperature clearly showed that there were more suitable conditions in wood for development and growth of fungi than indicated by air temperature and relative air humidity measurements.
Keywords: bakrove spojine; borove spojine; razkroj lesa; vlažnost lesa; zaščita lesa